Análise fenomenológica do relato de psicoterapeutas na escuta das vivências do luto por suicídio na clínica - CARVALHO , Ingrid Lorena Lima da Silva (2023)
The present study aimed to analyze how the psychotherapeutic attendance experience occurs, through psychotherapists’ view with people with people bereaved by suicide. Besides that, the specific objectives are: characterize the apoditic evidence regarding care for people bereaved by suicide, describe the feelings experienced by psychotherapists in the work with suicide grieving and to identify the changes in psychotherapists’ life experience as a result of attendance of these bereavement processes. The research was conducted through videoconferencing platforms as a result of the SARS-Cov-2 pandemic. The participants of the research were 6 psychotherapists who attended people bereaved by suicide, for a minimum period of 6 months, after the bereavement by suicide. This is a qualitative, exploratory research, based phenomenological method with a Husserlian guidance. The evidence showed that psychotherapists were directly affected by the follow-ups. Contact with patients bereaved by suicide allowed psychologists themselves to access the experiences of the bereaved and to seek to understand the life-death binomial. For this reason, professionals sought other supports, besides theory, such as: personal psychotherapy, supervision and the search for meaningful interpersonal ties, as a way to support their work. In this way, psychotherapists demonstrated that they can understand grief over suicide beyond the objectivity of the clinical space.